Mnemonics and Metaphorical Videos for Detecting/Diagnosing Musculoskeletal Sonopathologies - Jačisko, Jakub; Ricci, Vincenzo; Mezian, Kamal; Güvener, Orhan; Chang, Ke-Vin; Kara, Murat; Kobesová, Alena; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2023)
Musculoskeletal ultrasound identifies a broad range of pathologies. Typical sonographic images of certain pathological/abnormal conditions can be rendered and "highlighted" for the daily practice/language of musculoskeletal sonographers. The following text and accompanying figures/videos represent a collection of findings pertaining to commonplace pathological conditions. This article is the second part of a series-after the characteristic/metaphoric descriptions of normal musculoskeletal structures.
Keywords: Ultrasonography; ultrasonografie; Humans; Musculoskeletal System; muskuloskeletální systém; lidé